KASULINGGIHAN TEXT WRATI SASANA IN RELIGIOUS LIFE TRI SADAKA TRADITIONAL VILLAGES IN BALI - Anak Agung Gde Krisna Paramita; I Wayan Suka Yasa; I Gusti Bagus Wirawan (Dharmasmrti: Jurnal Ilmu Agama dan Kebudayaan, 2023)
The texts that contain the philosophy and ethics of kasulinggihan are very diverse, one of which is the Wrati sasana. Wrati sasana textis a teaching that contains rules, ethical teachings and taboos in Kasulinggihan's spiritual life, which is followed by Sulinggih. In accordance with the teachings of the Kasulinggihan sasana, contained in the wrati sasana has a complete concept. This study seeks to discussthe teachings of Wrati Sasana for Sulinggih in the religious life of Tri Sadaka in traditional villages in Bali, as well as the implementation of the teachings of Wrati Sasana by Sulinggih in the religious life of Tri Sadaka in traditional villages in Bali. These three aspects are then revealed by hermeneutic theory, phenomenological theory, and religious theory. The procedure for disclosing this research is using literature study techniques, interviews and observations. Analyzed with the stages of data reduction, data presentation, and drawing conclusions. This study found that the importance of the teachings of wrati sasana in the Kasulinggihan sasana order in the traditional villages of Bali Aga, Apanaga, and Bali Anyar, is used as a moral guide, ritual behavior guide and sulinggih tri sadaka self-control guide in traditional villages in Bali.